Acute generalized exanthematous pustulosis induced by icotinib: a case report and literature review - Yang, Wei; Zhao, Jiayu; Niu, Jun (Frontiers in Pharmacology, 2024)
Acute generalized exanthematous pustulosis, an infrequent adverse drug reaction, mainly results from drugs. Clinically, acute generalized exanthematous pustulosis manifests as a high fever, with skin lesions of small monomorphic subcorneal sterile pustules on an erythematous that presents at 1 to 4 days after medication exposure. The incidence of acute generalized exanthematous pustulosis varies from 3/1, 000, 000 to 5/1, 000, 000, while the mortality rate is typically around 5%. We present a case of a 69-year-old female who developed a diffuse, erythematous, pustular rash over the entire body and exhibited a fever of 38.3℃ after 4 days of icotinib therapy. Considering her medication history and the appearance of the lesions, she was diagnosed with acute generalized exanthematous pustulosis and received appropriate treatment. We also conducted a literature review through PubMed to compare similarities and differences between our case and those reported in the literature.